A Boneyard of Data:: Graffiti and Street Art’s Temporalities - MacDowall, Lachlan (Street Art & Urban Creativity, 2016)
In the era of Instagram, graffiti and street art are increasingly produced as digital objects, shaped by the architecture of digital platforms and the aggregated responses of audiences, transmuted into data. This paper focuses on one aspect of this context: the complex temporal existence of graffiti and street art - their duration, speed and acceleration – across multiple time zones. It asks: how is the consumption of graffiti and street art as digital images affecting its production? Has digital culture accelerated the production of graffiti and street art, driving shorter, faster cycles of repainting, with a greater ephemerality matched by parallel and potentially infinite lives on digital servers and devices? Using data generated over a period of 500 days at a single suburban painting site dubbed ‘the Boneyard’, this paper attempts to track the accelerating rhythms of graffiti in digital culture. It uses a number of methods to map the duration of pieces on walls and their digital echoes, including Photographic recording, data visualisation and social network analysis. Ultimately, this research seeks to extend existing methods of longitudinal analysis and to make a broader argument about the effects of social media on graffiti’s aesthetic features.